PERANCANGAN FASILITAS PEMBINAAN DAN REKREASI TUNANETRA DENGAN PENDEKATAN INDERA - Evangelista Putri Herlambang; Mekar Sari Suteja (Jurusan Arsitektur dan Perencanaan, 2023)
According to the Indonesian Ministry of Health, the blind population in Indonesia is estimated to be around 1.5% of the total Indonesian population, including those who are totally blind or have milder visual impairment. The Ministry of Women's Empowerment and Child Protection, explained that individuals with visual disabilities are those who have a visual clarity level of less than 6 per 60 after correction or have no visual ability at all. This significant amount is still not comparable to the provision of special facilities for the blind. Social discrimination is also experienced by blind people in Indonesia. In everyday life, children with visual impairments really need parental guidance and vice versa, parents who act as caregivers and intermediaries for children in the community must adapt to their child's condition. They need to learn a lot in assisting with special needs and monitoring the growth and development of their children. The design uses behavioral and narration methods through direct observation of the visually impaired which is very dependent on the senses of hearing and touch. The way the blind